Law Implementation of Basic Service to Minimum Service Standard Health In Banyumas Regency - Aqila Yufa Tsabita Hanani; Muhammad Taufiq; Ulil Afwa (Soedirman Law Review, 2023)
The Minimum Service Standard Health is the terms of the type and quality of basic health services that compulsory affairs of region which each citizen has to receive a minimum. In 2021, the Minimum Service Standard Health in some areas had not fulfilled 100% target, among them the Banyumas Regency. There are 2 (two) standards to be fulfilled by Banyumas District Health Office and Public Health in Banyumas Regency on 12 (twelve) types of basic health services. This research aims to analyze the implementation of basic service law to Minimum Service Standard Health in Banyumas Regency and factors that tend to affect it. This research is a qualitative research, with empirical juridical approach and descriptive research specs. Then the data is analyzed using qualitative method. The research results are measured in 4 (four) parameters, it shows that the implementation of basic service law to Minimum Service Standard Health in Banyumas Regency has been well managed, whic is held according to the standard, main task and function, authority, and a legal basis that applied. Nevertheless, in the practice it has not been fully accomplished in view of a few obstacles. As for factors that tend to influence the implementation of basic service law to Minimum Service Standard Health in Banyumas Regency are law factor; law enforcement factor; facility factor; society factor; and culture factor. In practice, these factors have a tendency that can support and/or hinder. The support factor are law factor and culture factor, while the obstacle factor are facility factor and society factor. The law enforcement factor can be categorized as both, the support factor and the obstacle factor.Keywords : Law Implementation, Minimum Service Standard Health, Support Factor, Obstacle Factor